The foreseeable future - Price, Reynolds 1933-2011 (Atheneum, 1991)
Three stories in which the characters must overcome great odds to have a promising future.
Keywords: Geschichte 1900-2000; Alltag, Brauchtum; USA; North Carolina -- Social life and customs -- Fiction; United States -- Social life and customs -- 20th century -- Fiction